Jews and the making of modern German theatre - Malkin, Jeanette R.; Rokem, Freddie, 1945- (Studies in theatre history and culture., 2010)
While it is common knowledge that Jews were prominent in literature, music, cinema, and science in pre-1933 Germany, the fascinating story of Jewish co-creation of modern German theatre is less often discussed. Yet for a brief time, during the Second Reich and the Weimar Republic, Jewish artists and intellectuals moved away from a segregated Jewish theatre to work within canonic German theatre and performance venues, claiming the right to be part of the very fabric of German culture. Their involvement, especially in the theatre capital of Berlin, was of a major magnitude both numerically and i.